Structural insights into light harvesting by antenna-containing rhodopsins in marine Asgard archaea - Tzlil, Gali; Marín, María Del Carmen; Matsuzaki, Yuma; Nag, Probal; Itakura, Shota; Mizuno, Yosuke; Murakoshi, Shunya; Tanaka, Tatsuki; Larom, Shirley; Konno, Masae; Abe-Yoshizumi, Rei; Molina-Márquez, Ana; et al. (Nature microbiology, 2025)
Aquatic bacterial rhodopsin proton pumps harvest light energy for photoheterotrophic growth and are known to contain hydroxylated carotenoids that expand the wavelengths of light utilized, but these have not been characterized in marine archaea. Here, by combining a marine chromophore extract with purified archaeal rhodopsins identified in marine metagenomes, we show light energy transfer from diverse hydroxylated carotenoids to heimdallarchaeial rhodopsins (HeimdallRs) from uncultured marine planktonic members of 'Candidatus Kariarchaeaceae' ('Candidatus Asgardarchaeota'). These light-harvesting antennas absorb in the blue-light range and transfer energy to the green-light-absorbing retinal chromophore within HeimdallRs, enabling the use of light that is otherwise unavailable to the rhodopsin. Furthermore, we show elevated proton pumping by the antennas in HeimdallRs under white-light illumination, which better simulates the light conditions encountered by these archaea in their natural habitats. Our results indicate that light-harvesting antennas in microbial rhodopsins exist in families beyond xanthorhodopsins and proteorhodopsins and are present in both marine bacteria and archaea.
Keywords: archeální proteiny; Carotenoids; Rhodopsins, Microbial; Phylogeny; přenos energie; světlo; Light-Harvesting Protein Complexes; Archaea; karotenoidy; Energy Transfer; Light; rodopsin; Aquatic Organisms; Archaeal Proteins; Seawater; fylogeneze; světlosběrné proteinové komplexy; metagenom; rhodopsiny mikrobiální; vodní organismy; mořská voda; Metagenome; Rhodopsin